2015
DOI: 10.1088/0031-9155/60/23/9185
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of dose distribution in compressible breast tissues using finite element modeling, Monte Carlo simulation and thermoluminescence dosimeters

Abstract: Compression is a technique to immobilize the target or improve the dose distribution within the treatment volume during different irradiation techniques such as AccuBoost(®) brachytherapy. However, there is no systematic method for determination of dose distribution for uncompressed tissue after irradiation under compression. In this study, the mechanical behavior of breast tissue between compressed and uncompressed states was investigated. With that, a novel method was developed to determine the dose distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
(87 reference statements)
1
5
0
Order By: Relevance
“…In addition, the prosthesis shows a good distribution of stress. [44], 14 [24] It can be observed that the displacement values (in the proposed prosthesis) are within the results reported by similar research. The differences presented in the values are due to the dimensions, materials and conditions of each computational model or experimental model that were used.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…In addition, the prosthesis shows a good distribution of stress. [44], 14 [24] It can be observed that the displacement values (in the proposed prosthesis) are within the results reported by similar research. The differences presented in the values are due to the dimensions, materials and conditions of each computational model or experimental model that were used.…”
Section: Resultssupporting
confidence: 86%
“…[20]. There are diverse scientific and technological advances in the literature that provide computational models and finite element models focused on simulating the mammary gland for preclinical evaluation, prevention, training, diagnostic [21][22][23][24][25][26][27][28][29][30][31] or on analyzing the biomaterials used for implant reconstruction [14,15,32]. In the case of the most advanced computational models of a breast for the simulation of the anatomy is the anthropomorphic software breast phantom.…”
mentioning
confidence: 99%
“…1H). [102][103][104][105] For rectal cancer, several articles have discussed ICMA with a central shielding rod (tungsten, 8 mm in diameter, surrounded by 8 channels through which 192 Ir sources can be translated; Fig. 1G).…”
Section: Static-shielded Applicatorsmentioning
confidence: 99%
“…The advantage of Artificial Neural Networks (ANN) is good accuracy, as they are trained by the data of different centers [10] and in a large number and measure the air kerma automatically so that in the mentioned model, there is no need to dosimeter and trained operators and is also more user-friendly. Furthermore, it decreases the computational error and the difference between the absorbed dose measured by dosimetry and computational method of Monte-Carlo simulation method [11].…”
mentioning
confidence: 99%